Design of an intelligent sensor network for micro-grid - Yu, Yu Soe. (2011)
Nowadays, many countries establish renewable distributed energy systems to contribute electric power to many different loads such as schools, residents and industries. A distributed energy system normally consists of a number of small-scale distributed energy sources such as fuel cells, micro-turbines and solar photovoltaics and wind turbines to produce electric power at locations near to customers.